Using speech intelligibility scores to rate sound insulation - Park, Hyeon Ku; Bradley, John S.; Gover, Bradford N. (Canadian Acoustics, 2007)
Sound insulation ratings have been measured by using speech intelligibility of transmitted speech as speech is a common type of disturbing sound and because speech intelligibility tests can provide accurate subjective ratings. Airborne sound insulation is usually rated in terms of the ISO Weighted Sound Reduction Index (Rw) or the ASTM Sound Transmission Class (STC). Measures in which decibel values are arithmetically averaged over a range of frequencies were all generally quite successful. However, results tended to be less successful, when measures included energy averaging of values at various frequencies. The arithmetic average transmission loss measure AA(200-2.5k) and the Rw measure with the new spectrum weighting term provided very good relationships with mean speech intelligibility scores and are considerable improvements over existing standard measures. The new spectrum weighting is also appealing because it adds to an existing standardized approach.